Redox-active cathode interphases in solid-state batteries. Issue 43 (25th October 2017) - Koerver, Raimund; Walther, Felix; Aygün, Isabel; Sann, Joachim; Dietrich, Christian; Zeier, Wolfgang G.; Janek, Jürgen
Abstract : In situ X-ray photoelectron spectroscopy shows the redox-active chemistry of β-Li3 PS4 at the cathode interface in a solid-state battery. Abstract : All-solid-state batteries are expected to provide a next-generation solution for energy storage. Employing fast conducting lithium thiophosphates as a replacement for liquid electrolytes in conventional lithium ion batteries has shown great promise, however, capacity fading and the underlying interfacial side reactions of thiophosphates and cathode active materials are not yet understood well. In this study, we charge solid-state batteries to different cut-off potentials and find the formation of a redox-active resistive layer in the solid electrolyte, which impedes the conductivity depending on the state-of-charge of the battery. Using electrochemical impedance spectroscopy as well as depth profiling with X-ray photoelectron spectroscopy we find a thick passivation layer at the current collector and decomposition products within the cathode composite. In addition, an in situ electrochemical experiment during X-ray photoelectron spectroscopy shows that the solid electrolyte is redox active at the cathode/solid electrolyte interface in solid-state batteries. This work highlights the importance of protecting interface layers at the current collector, and the influence of the resulting electric potential drop, as well as provides insight into the redox chemistry of lithium conducting thiophosphates.